Pemanfaatan Microsoft Excel dalam Membantu Penyusunan Laporan Keuangan di MI Ngalian Tirto Pekalongan - Rikko Aji Setiawan; Rizqi Mursalina; Novianti Putri Rahmadani; Hendri Hermawan Adinugraha (Journal of Innovation and Community Engagement, 2022)
The role of Information and Communication Technology is very much needed for school institutions as their provision in dealing with the changes and demands of the times in the era of the Industrial Revolution 4.0. Operating a computer is part of the hard skills. Students and teachers need to have skills in operating the programs contained in Microsoft Windows and the program that is most often used is Microsoft Excel. This particular program can support daily work as it makes processing data and compiling financial reports easier. Through Microsoft Excel, financial reports can be prepared simply with a shorter cycle, from journaling to simple financial reports. The purpose of this community service is to provide training on the process of preparing financial reports through Microsoft Excel in order to streamline administrative performance. The method used in this service is in the form of training and direct practice. The subject of this training is the financial treasurer section of MI Ngalian Tirto. The results of this service indicate that this training provides knowledge for school treasurers regarding simple accounting processes by utilizing excel so that in preparing financial reports can be better.